Strategi Pemasaran Usaha Art Shop Lokal Di Desa Tegallalang Kabupaten Gianyar - Saputra, Pande I Putu Angga; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p18, 2018)
Art shop in Tegallalang is one of the businesses that were built by the community with a small capital as well as the livelihoods of local communities. The expansion of the art shop in Tegallalang causing the large number of tourists visiting Tegallalang, it is also supported by the presence of a tourism destination with the beauty of rice fields across the village that is known for its slender stones. This research uses qualitative descriptive method, i.e. by doing interviews, observation, documentation, library studies and questionnaires. The technique of determination of informants used is purposive sampling technique and determination of the sample using the quota sampling and accidental sampling. The result of this study show a marketing strategy that can be used by traders to face competition that is creating cultural tourism atttractions activities, introducing product manufacturing techniques to consumer, improving the ability in technologi, providing parking lots and transit places, providing facilities that can facilitate employes in work, improving quality or multiplaying product models, working with other in buying raw materials, make arrangement of prices agreement with other art shop and angage in English training.   Keywords: Businesses, local Art shop, marketing strategies, and competitiveness